Boundary layer and heat transfer Williamson fluid flow over a stretching sheet with Newtonian heating - et. al., B.Shankar Goud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Aligned magnetic field with Williamson fluid has been analyzed using a stretching sheet with Newtonian heating. The governing partial differential equations are transformed to the nonlinear ordinary differential equation by employing the similarity transformations and then solved by using the MATLAB inbuilt solver bvp4c. The influence of various parameters on dimensionless velocity and temperature was graphically explored. Comparisons of all conditions for a particular situation have been made and a very effective agreement has been reached.